The Modeling Structural Test Anxiety Based on Perfectionism with Mediating Role Fear of Negative Evaluation in Students in Tehran City - Bahman kord; kourosh jabbari; arezoo oskoei (مطالعات روانشناسی تربیتی)
The purpose of this study was to modeling structural test anxiety based on perfectionism with mediating role fear of negative evaluation in students in Tehran city. The statistical population of the research consisted of all male students of the first year of high school in Tehran in the academic year of 1400-1401, and 500 people were selected by calculating the sample size in structural equations and using available sampling method. To measure the variables, test anxiety inventory (TAI) of Abolghasemi and et al (1996), multidimensional perfectionism scale (MPS) of Hewitt and Flett (1991) and brief fear of negative evaluation scale (BFNE) of Leary (1983). Data were analyzed using Pearson correlation and structural equation modelling with using SPSS-24 and AMOS software was investigated. The results showed that there is a positive and significant relationship between perfectionism and fear of negative evaluation with test anxiety (P <0.01). The results also showed that most of the direct paths of this study were significant and the indirect paths of perfectionism were significant through the mediating role of fear of negative evaluation on test anxiety. Also, proposed model had an acceptable fitness to the data (RMSEA=0/058, P-value<0/05). The results of this research show that perfectionism has a significant effect on exam anxiety and fear of negative evaluation acts as an important mediator in this relationship. These findings emphasize the importance of paying attention to psychological factors in managing students' exam anxiety and can help to develop effective strategies to reduce anxiety in educational environments